PERANCANGAN KURSI LIPAT MENGGUNAKAN SOLIDWORKS - Engkos Koswara (PROCEEDING STIMA)
Folding chair is a chair that is lightweight , portable , and can be folded flat so that the number of seats can be assembled into a single stack while stored . Folding chairs are often used because its ldesign is simple and efficient . In that sense , it is very flexible and portable . When used you stay open , if not then you can simply fold it back . Store them is not difficult, you simply take advantage of the gaps that exist . The material is diverse , ranging from teak , plastic , aluminum pipe , and so on. Each has endurance and strength are different.The use of material on folding chairs are very influential on the strength of folding chairs. For wood materials received the greatest stress was 6689 kN/m2, 12.9 mm displacement and strain of 5,5x10-5. For aluminum material that received the greatest stress was 6713 kN/m2, 0,56 mm displacement and strain of 1,2x10-3.Keywords : folding chair , solidwork , material